Pemanfaatan Visualisasi Data dalam Meningkatkan Pengambilan Keputusan Bisnis - Siti hidayatul Khoirun Nisa'; Rusdianto, R. Yuniardi (Politeknik Negeri FakFak, 2024)
In today's fast-paced business environment, decision makers face the challenge of processing large amounts of data to make accurate decisions. Data visualization has emerged as a powerful tool to help organizations overcome these challenges. By presenting data in a visually appealing and easy-to-understand format, decision makers can quickly gain insights into complex data sets and make informed choices that drive business growth. This analysis aims to explore the impact of data visualization on business decision-making, focusing on the benefits of data visualization. This data analysis method will specifically investigate how data visualization can improve the decision-making process in the context of complex and large data sets, offering valuable insights in optimizing business operations. Demonstrating that interactive data visualization platforms such as Tableau play an important role in improving decision-making by providing real-time insights, identifying market trends, and enabling faster response to changes.